Explorando pérdidas de momento angular y la estabilidad en la transferencia de masa en binarias interactuantes - Echeveste, Maite (2023)
We study low-mass X-ray binary systems (LMXB). In this type of binaries, a low-mass star transfers mass to a compact object via Roche Lobe overflow. Magnetic braking is of great importance when studying angular momentum loss from the system. Here, we select four different prescriptions that present different intensities and study their effect on the evolution of the binaries. Finally, we study the possibility of the studied systems forming wide and tight binaries maintaining a stable mass transfer phase.